Intergenerational theatre: Blending ages/creating connections. Storytelling to connect the generations - Bailey, Sally D. (My University, 2009)
As an outgrowth of a drama group at Meadowlark Hills Retirement Community, group of older adults created stories about growing up during the Depression which they shared in storytelling sessions with classes of elementary school students in Manhattan, Kansas. Teachers were excited by the first- person connections about history that were made with their students, as well as the intergenerational component, children learned what it was like growing up seventy years ago, and the storytellers enjoyed passing on their life experiences to a younger generation.
Keywords: Storytelling; Intergenerational; Drama; Older adults